Upaya Pemenuhan Hak Restitusi Korban Tindak Pidana Perdagangan Orang pada Tahap Penuntutan - Fuad Nur (CV. Ulil Albab Corp, 2023)
This study aims to analyze in depth the implementation of the role of public prosecutors in efforts to fulfill restitution rights for victims of trafficking crimes and inhibiting factors in efforts to fulfill the rights of reconstitution for trafficking victims at the prosecution stage. The type of research is normative and juridical, accompanied by interview data. The approaches used are the statutory approach and the case approach. This study specifically analyzed data from the Makassar State Prosecutor’s Office, the Maros State Prosecutor’s Office, and the Makassar District Court. The data analysis technique used is qualitative through reasoning and legal argumentation. In conclusion, the public prosecutor has so far not exercised its role optimally in fulfilling the right to restitution for trafficking victims. As can be seen, there are no trafficking defendants prosecuted for restitution in South Sulawesi, so victims' rights to compensation in the form of restitution tend to be ignored. The obstacle to fulfilling the right to reconstitution is that the public prosecutor still uses the Criminal Procedure Code as a whole and is not responsive to other regulations that guarantee the right to restitution for victims. The public prosecutor is only limited to solving criminal cases by finding the material truth of the criminal acts committed by the accused without considering the losses suffered by the victim. Requests for restitution that must go through the Witness and Victim Protection Agency (LPSK) can make it difficult for public prosecutors to coordinate.